ANALISIS RASIO PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT. AMANAH FINANCE - Andi Marlinah (AkMen JURNAL ILMIAH, 2014)
This study aims to analyze the financial performance PT. Amanah Finance in terms of profitability in the year 2010 to 2012. Based on the results of the study, the analysis of profitability seen from the gross profit margin from 2010 to 2012 increased slightly, and the views from the net profit margin increased. The financial performance of the companies seen from ROI and ROE has increased, but the level of ROI and ROE of the company is said to poor or unstable because it is still relatively far from the industry standards average. From the results of this analysis, it is suggested that the management of PT. Amanah Finance need to analyze the financial statements in each period and management also needs to conduct a thorough evaluation of the profitability of the company in order to achieve the ratio of the average industry standards average.